Static penetration test for historical masonry mortar. (30th September 2016) - Liberatore, Domenico; Masini, Nicola; Sorrentino, Luigi; Racina, Vito; Sileo, Maria; AlShawa, Omar; Frezza, Luca
Highlights: A static penetration test for historical masonry mortar is presented. The test provides the penetration load as a function of the penetration depth. Experiments were performed on five historical buildings with decayed mortar. Penetration tests are compared with direct shear and percussion penetration tests. Abstract: The penetration test for historical masonry mortar presented in this study is based on the principle of "static" penetration. A pin is driven at constant velocity by a stepper motor controlled by a computer. The test result is the penetration load as a function of the penetration depth. The penetrometer has been tested on masonry walls consisting of decayed mortar. The objective of the test is to provide information about the mechanical characteristics of mortar (friction coefficient, cohesion). To this end, the results are compared with those from direct shear tests on mortar samples and with those from a previous percussion penetration test.